Investigating Oxidative Stress and Antioxidant Dynamics in Beta-thalassemia Major: A Comparative Study from Al-Diwaniyah, Iraq - Hadeer Hayder Inteek; Shaymaa Rabeea Madhkhoor (Journal of Applied Hematology)
BACKGROUND: Beta-thalassemia major (β-TM) is a severe blood disorder in which the body does not make enough hemoglobin, leading to chronic anemia and the need for regular blood transfusions. This status induces iron overload from transfusions that can lead to the onset of oxidative stress and hence worsen cellular impairment. Oxidative stress is combated by antioxidants that precedes oxidostasis study aimed to evaluate the relationship between antioxidant levels and β-TM in patients from Al-Diwaniyah Governorate (reason) Iraq. MATERIALS AND METHODS: This study was carried out on 60 patients; β-TM had been diagnosed and treated at the Center of Genetic Disease in Al-Diwaniya. A control group of 45 age- and gender-matched healthy controls was also recruited. The levels of the main antioxidants, which included catalase (CAT), human glutathione (GST), and malondialdehyde (MDA) – superoxide dismutase (SOD) were also analyzed from the blood samples obtained. RESULTS: Compared with the control group, patients with β-TM showed significantly higher MDA levels and increased activity of GST, CAT, and SOD P < 0.05. Patients all had elevated levels of serum ferritin, indicating iron overload. A highly significant inverse correlation between ferritin and antioxidants (P < 0.01) characterizes higher iron overload correlates with better antioxidant defenses. Frequent transfusions were also associated with increased depletion of antioxidant pools. CONCLUSION: A significant oxidative stress in β-TM affecting SOD, CAT, MDA, and glutathione levels was demonstrated in this study. This supports the role of oxidative stress in the pathophysiology of the disorder and offers possible interventions to reduce oxidative insults in affected individuals.